Pengaruh Karakteristik Sharia Marketing terhadap Minat Menabung Nasabah di Bank Syariah Indonesia (BSI) KCP Pinrang - Syahriyah Semaun; Musdalifah Musdalifah; Sitti Cheriyah Rasyid; Rukiah Rukiah (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2022)
The study aimed to expouse the influence of Sharia Marketing characteristics which consists of Theistic (Rabbaniyyah), Ethical (Akhlaqiyyah), Realistic (Waqi'yyah) and Humanistic (Insaniyyah) variables on the interest of saving, and to find out the dominant variable that simultaneously influences on the characteristics of Sharia Marketing in the interest of saving. The research applied a quantitative research through descriptive method. The data collected by distributing questionnaires. The Multiple Regression Analysis method used to test the research hypothesis. The results of the study found as follows; (1) the Theistic (Rabbaniyyah) variable has a positive and insignificant influence on the variable of interest in saving, (2) the Ethical (Akhlaqiyyah) variable has a positive and insignificant influence on the variable of interest in saving, (3) the Realistic (Al-Waqi'yyah) variable has a positive and insignificant influence on the variable of interest in saving, and finally, (4) the Humanistic (Al-Insaniyyah) variable has a positive and significant influence on the variable of interest in saving and the Humanistic (Al-Insaniyyah) variable has the most dominant influence simultaneously on the interest of saving.